Study of open cholecystectomy for gallbladder disorders - Kumar, Sunil; Reddy, T. Rudra Prasad (International Surgery Journal, 2021)
Background: Cholecystectomy is one of the most common surgeries done worldwide. Most common indication is biliary colic due to cholelithiasis. Presently most cholecystectomies are done by laparoscopic approach, however conversion to open cholecystectomy is needed in few circumstances and there are some absolute indications for open cholecystectomy where laparoscopic procedure can’t be done. Methods: This is a prospective observational study of 50 open cholecystectomies operated during March 2017 to Feb 2019 in our medical college. Various data including demographic data of patients, different indications, post-operative complications were documented and analyzed. Results: Mean age of the patients was 40.58 (16-65) years. Female patients were more in number 32 (64%) when compared with males. Maximum patients were in the age group 31-40 years accounting to 17 (34%) of study population. Pain abdomen 24 (48%) was the chief presenting complaint. Cholelithiasis 38 (76%) was the major indication for surgery. Complications like bile leak, bleeding, subphrenic abscess and infection occurred in 04 (08%) patients. Total four cases of laparoscopic cholecystectomy were converted to open cholecystectomy. Mean hospital stay was 7.48 (5-14) days. Conclusions: Even though laparoscopic cholecystectomy is the gold standard in the present era, it is important that the surgeon is also competent in doing open cholecystectomy. Certain conditions require planned open cholecystectomy as the standard procedure. In difficult laparoscopic cases, the surgeon must take timely decision to convert to the open technique. Surgeons experience and proper clinical judgment skills are important in difficult cases.